E-commerce Sparepart Mobil (Studi Kasus Toko Sahabat Motor) - Candra Gunawan; Indra Kanedi; Ricky Zulfiandry (UNIVED Press, 2025)
Abstract—E-commerce-based sales information system at Toko Sahabat Motor, to overcome the problems of the conventional sales system used before. This system is designed to provide convenience in managing product data, transactions, and store information in integrated manner, as well as making it easier for customers to obtain information and online purchase car spare parts. The research uses the waterfall method, with steps such as requirements analysis, design, implementation, and system testing using the black-box testing method. The results showed that the information system built can improve store operational efficiency, provide faster and more accurate services, and support digital marketing strategies. The system is also designed with key features such as product data management, user registration, order processing, and payment options via COD and bank transfer, which are relevant to meet the needs of customers in the target area. Keywords :E-Commerce, Information System, Online Sales